2018
DOI: 10.1021/acs.energyfuels.7b02298
|View full text |Cite
|
Sign up to set email alerts
|

Ash Formation and Fouling during Combustion of Rice Husk and Its Blends with a High Alkali Xinjiang Coal

Abstract: Limited data from fluidized bed combustion tests have shown that rice husk, a silicon-rich residual biomass, has the potential to be cofired with coal while not inducing unacceptable ash-related problems. However, there is great concern regarding the behavior of rice husk ash under pulverized fuel combustion conditions, where the temperatures are much higher and expected to facilitate fuel interactions. This work, to the authors' knowledge, is the first to investigate both ash formation and fouling behavior in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 35 publications
1
26
1
Order By: Relevance
“…The above analysis results confirm that the self-desulfurization capacity of fuel ash is largest at 50% M b and the co-combustion of coal and biomass has a synergistic effect under pressurized oxy-fuel condition, which is probably because the alkali metal and alkaline earth metal oxides in biomass fuel such as CaO and K 2 O react with gaseous SO 2 . Different from the experimental result in this study, the content of SO 3 in the fuel ash in other studies increased or decreased with the increase of M b . The results of the XRF and XRD analyses point out that there are lower contents of K 2 O and Na 2 O and no MgSO 4 and Na 2 SO 4 in the fuel ash, which may be because the fuel has a relatively low content of Mg and Na.…”
Section: Results and Discussioncontrasting
confidence: 99%
“…The above analysis results confirm that the self-desulfurization capacity of fuel ash is largest at 50% M b and the co-combustion of coal and biomass has a synergistic effect under pressurized oxy-fuel condition, which is probably because the alkali metal and alkaline earth metal oxides in biomass fuel such as CaO and K 2 O react with gaseous SO 2 . Different from the experimental result in this study, the content of SO 3 in the fuel ash in other studies increased or decreased with the increase of M b . The results of the XRF and XRD analyses point out that there are lower contents of K 2 O and Na 2 O and no MgSO 4 and Na 2 SO 4 in the fuel ash, which may be because the fuel has a relatively low content of Mg and Na.…”
Section: Results and Discussioncontrasting
confidence: 99%
“…They reported that different slagging levels can be observed in different biomasses due to their distinctive concentrations of K, Si, and Ca in their fuel compositions . Reducing the concentrations of alkali metals, K in particular, prior to combustion can considerably decrease the ash-melting tendency and slag formation. , Thus, a selective pretreatment can effectively mitigate the ash-melting tendency of biomass fuels. There are few investigations in the generation of biogenic silica from RH using surface-sensitive methods to confirm the high purity of the generated silica .…”
Section: Introductionmentioning
confidence: 99%
“…A large volume of studies has been carried out on ash fusion characteristics of coal and biomass ash, mainly involving AFTs, 14–16 mineral phases, 17,18 and their interactions of coal/biomass ash, 19,20 as well as the evolution of troublesome elements 3,21,22 . The research on ash fusion characteristics is usually associated with the analysis of AFTs obtained from high‐temperature fusion test.…”
Section: Introductionmentioning
confidence: 99%